2022
DOI: 10.36909/jer.18695
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of groove shape on the tensile strength of commercial steel

Abstract: In industry, welding is well known. There is a great demand for effective and quality welding. Manufacturers seek to remain competitive in the market. They rely on their manufacturing engineers and production personnel to quickly and effectively set up manufacturing processes for new products. Gas metal arc welding is one of the most widely used processes in the industry. Input factors such as welding current, welding voltage, Gas flow rate, wire feed speed, wire size and welding speed play a significant role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 5 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Previous similar studies concluded that tensile strength increased with decreasing welding voltage, welding current, and WFS [19,20,21]. The groove shape was also reported to affect the mechanical properties of welding, where V-shaped welding obtained higher tensile strength and hardness than double V-shaped welding [20].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous similar studies concluded that tensile strength increased with decreasing welding voltage, welding current, and WFS [19,20,21]. The groove shape was also reported to affect the mechanical properties of welding, where V-shaped welding obtained higher tensile strength and hardness than double V-shaped welding [20].…”
Section: Introductionmentioning
confidence: 85%
“…The relationship between tensile strength and hardness was reported before [19,20,21]. Calderón et al (2021) concluded that the tensile strength and hardness of FZ and HAZ were also studied because they affect the mechanical properties of welding due to the different properties of the welding and adjacent regions [22].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, Talabi et al [12] concluded that the welding that has higher tensile strength has lower hardness. In general, both the tensile strength and hardness of the welding decrease with the increase of the welding voltage and current [13,14]. Because of the increase, it increases the heat input in the weld pool, causing internal stresses in the fusion zone (FZ) and HAZ and consequently the welding's mechanical properties' deterioration such as tensile strength and hardness while the toughness increases [11].…”
Section: Introductionmentioning
confidence: 99%